Age-based stereotype threat effects on dynamic balance in healthy older adults - Borel, Liliane; Alescio-Lautier, Béatrice; Léonard, Jacques; Régner, Isabelle (Frontiers in Systems Neuroscience, 2024)
Introduction: Stereotype threat can lead older adults to perceive their experiences in a biased manner, giving rise to interfering thoughts and negative emotions that generate stress and anxiety. Negative beliefs about aging may serve as an additional factor that increases the need for attentional demand, potentially resulting in a performance level below their actual capabilities. In the present study, we asked whether negative aging stereotypes influence a dynamic balance task and explored the means to counteract them in healthy elderly participants. Methods: The performance of balance was compared in two groups of participants aged 65 to 75 years (n=22) under stereotype threat or reduced-threat situation. Balance abilities were tested under dynamic conditions, requiring participants to maintain balance on a moving platform and using a gradient of difficulty (with eyes open or closed, without or with foam). Postural performance was evaluated by means of posturographic evaluation of the center of pressure displacement and motion analysis. Additionally, we investigated the effects of stereotype threat on walking tasks at preferred speeds and on the Timed Up and Go (TUG) test. Results: Participants under stereotype threat showed poorer balance, particularly in challenging conditions (eyes closed, on foam), with less effective body segments stabilization. Their postural stabilization on foam was worse compared to a solid surface. Conversely, those in the reduced threat condition maintained better body segment stabilization across all conditions, indicating consistent postural control regardless of the presence of foam. Stereotype threat did not affect preferred walking speed or the time to complete the "Time Up and Go" test. Discussion-Conclusion: This study provides the first description of age-based stereotype threat effects on a dynamic balance task and how to counteract them in healthy older adults. We suggest that the decrease in postural performance observed in participants exposed to stereotype threat can be attributed to a split in attentional focus between negative intrusive thoughts and the attention needed for maintaining balance. These findings open new perspectives on how to overcome negative expectations when evaluating and training physical abilities, thereby contributing to fall prevention among older adults.